Neutrino nonstandard interactions and lepton flavor universality violation at SND@LHC via charm production - Bhubanjyoti Bhattacharya; Alakabha Datta; Elena Graverini; Lopamudra Mukherjee; Divya Sachdeva; John Waite (Journal of High Energy Physics)
Abstract In this work, we explore the effect of neutrino nonstandard interactions (NSI) involving the charm quark at SND@LHC. Using an effective description of new physics in terms of four-fermion operators involving a charm quark, we constrain the Wilson coefficients of the effective interaction from two and three-body charmed meson decays. In our fit, we include charmed meson decays not only to pseudoscalar final states but also to vector final states and include decays to the η and η ′ final states. We also consider constraints from charmed baryon decays. We then study the effect of new physics in neutrino scattering processes, involving charm production at SND@LHC, for various benchmark new physics couplings obtained from the low energy fits. Finally, we also study the effects of lepton universality violation (LUV) assuming that the new physics coupling is not lepton universal.